Augmented screening of sunflower inbreds for Alternariaster leaf blight disease under polyhouse conditions: Augmented screening of sunflower inbreds for Alternariaster leaf blight disease under polyhouse conditions - K SAKTHIVEL; H P MEENA; M SUJATHA; R D PRASAD (Journal of Oilseeds Research, 2023)
A total of 206 sunflower inbreds were screened for Alternariaster leaf blight resistance under poly house conditions. The results showed that eight sunflower inbreds including maintainer line, prebred lines and restorer lines viz., HA24B, PB-898, PB-904, PB-205, PB-905, ID-32, PB-889, RGP-278-2 showed tolerant reaction to Alternariaster leaf blight and able to set good seeds under high pathogen pressure.